Phân tích sự ảnh hưởng của đặc điểm video quảng cáo trực tuyến trên nền tảng Youtube lên sự bị xâm nhập của người xem dẫn đến hành động bấm bỏ qua hay xem tiếp - Đinh Tiên , Minh; Nguyễn Đoàn Nam , Hân; Trần Cát , Tường; Võ Huỳnh Song , Thi; Nguyễn Lê Hoài , Phương; Bùi Thị Ngọc , Huyền (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
This research is conducted to analyze the effects of the YouTube online advertising videos’ characteristics on viewers’ intrusiveness through ad avoidance or ad engagement. This study applies the method of using secondary data sources and primary data through survey method. Structural equation modeling (SEM) is applied based on a sample of 434 observations chosen by stratified sampling. The result of research shows that Informativeness and Ad Length, which have a low or even no effect on viewers’ Intrusiveness, while factors like Ad Format, Celebrities and Ad Relevance all have significant effects on viewers. This research also provides practical management implications to help businesses develop the quality of an online video advertisement through these main factors: Ads Format, Celebrities in the ads, and Ad Relevance with the aim to increase the effectiveness of online video ads on the YouTube platform. In addition, businesses need to have a clear awareness of the importance of the Intrusiveness that YouTube video ads have an effect on viewers’ actions.